2020
DOI: 10.1016/j.jjcc.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Association between calf girth and peripheral artery disease in the Atherosclerosis Risk in Communities Study

Abstract: Background: The pathogenesis of peripheral artery disease (PAD) is associated with impaired calf muscle. We sought to investigate the association between gender-specific calf girth and the prevalence of PAD among participants from a community-based cohort study. Methods: A total 13,808 participants in the Atherosclerosis Risk in Communities (ARIC) study without prior PAD were included in the final analysis. Calf girth was measured at baseline (1985)(1986)(1987). A hospital diagnosis with an ICD-9 code defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Based on previous literature [ 8 , 24 , 25 ], PAD-related hospitalizations were identified by the following International Classification of Diseases Ninth Revision (ICD-9) discharge codes: peripheral vascular disease, unspecified (443.9); atherosclerosis of native arteries of the extremities, unspecified (440.20); atherosclerosis of native arteries of the extremities with intermittent claudication (440.21); atherosclerosis of native arteries of the extremities with rest pain (440.22); atherosclerosis of native arteries of the extremities with ulceration (440.23); atherosclerosis of native arteries of the extremities with gangrene (440.24); other atherosclerosis of native arteries of the extremities (440.29); atherosclerosis of bypass graft of the extremities (440.3); chronic total occlusion artery extremities (440.4); atherosclerosis of other specified arteries (440.8); coexisting leg amputation (84.11, 84.12, 84.15, 84.17); leg artery revascularization (38.18, 39.25, 39.29, 39.50); lower extremity ulcer and gangrene (707.1x). Incident PAD was defined as the first hospitalization with diagnosis of PAD or a new onset of measured ABI < 0.90 during follow-up visits [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous literature [ 8 , 24 , 25 ], PAD-related hospitalizations were identified by the following International Classification of Diseases Ninth Revision (ICD-9) discharge codes: peripheral vascular disease, unspecified (443.9); atherosclerosis of native arteries of the extremities, unspecified (440.20); atherosclerosis of native arteries of the extremities with intermittent claudication (440.21); atherosclerosis of native arteries of the extremities with rest pain (440.22); atherosclerosis of native arteries of the extremities with ulceration (440.23); atherosclerosis of native arteries of the extremities with gangrene (440.24); other atherosclerosis of native arteries of the extremities (440.29); atherosclerosis of bypass graft of the extremities (440.3); chronic total occlusion artery extremities (440.4); atherosclerosis of other specified arteries (440.8); coexisting leg amputation (84.11, 84.12, 84.15, 84.17); leg artery revascularization (38.18, 39.25, 39.29, 39.50); lower extremity ulcer and gangrene (707.1x). Incident PAD was defined as the first hospitalization with diagnosis of PAD or a new onset of measured ABI < 0.90 during follow-up visits [ 3 ].…”
Section: Methodsmentioning
confidence: 99%
“…Their fates have been also documented in clinical guidelines, including the Trans-Atlantic Inter-Society Consensus (TASC) [8] , TASC II [9] , and, most recently, the Global Vascular Guidelines [1] . Furthermore, many studies reported clinical features and survival rates relevant to peripheral artery disease in various clinical settings [10][11][12][13][14][15][16] . By contrast, features of the contralateral limb, especially an asymptomatic one, in CLTI patients undergoing revascularization are yet to be clearly illustrated.…”
Section: Introductionmentioning
confidence: 99%